Renewable energy: water-land nexus, food-biofuels tradeoffs - Ringler, Claudia (2023)
Claudia Ringler, Environment and Production Technology Division, IFPRI April 19, 2022 | Penn State University WEF Nexus 597 (003 LEC, Class 27525)